2019
DOI: 10.15331/jdsm.7086
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Educational Intervention of Dental Hygiene Students

Abstract: Study Objectives: Oral health professionals (OHPs) have a unique opportunity to screen for obstructive sleep apnea (OSA) but receive limited education about OSA. This study determined whether an online educational intervention could significantly increase the knowledge of information relevant to OSA screening in individuals studying dental hygiene (DH). 1 Methods: A 17-question, comprehension-based pretest and posttest assessed OSA knowledge. The convenience sample consisted of students enrolled in the first y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…al., (Valerio & Heaton, 2014) included concepts on the significance of OSA knowledge, analysis of OSA signs and symptoms, and evaluate clinical symptoms, 16 while Glueckertet. al., (Glueckert et al, 2019) focused on OSA definition, background including symptoms, associated health conditions and consequences, diagnosis, screening methods, and treatment options, along with a case study. The effectiveness of the teaching method employed in the current study was evident with the significant (increase in mean knowledge post-test when compared to the pre-test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., (Valerio & Heaton, 2014) included concepts on the significance of OSA knowledge, analysis of OSA signs and symptoms, and evaluate clinical symptoms, 16 while Glueckertet. al., (Glueckert et al, 2019) focused on OSA definition, background including symptoms, associated health conditions and consequences, diagnosis, screening methods, and treatment options, along with a case study. The effectiveness of the teaching method employed in the current study was evident with the significant (increase in mean knowledge post-test when compared to the pre-test.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant improvement in OSA knowledge scores was observed in a study conducted among dental hygiene students, where the mean pre-test score was increased post-test. (Glueckert et al, 2019) A recent study conducted on nurse-practitioner students also revealed significant improvement in sleep knowledge, after going through case-based modules that addressed sleep health and disorders. (Sawyer AM et al, 2022) This highlights the overall need of educating young practitioners and students regarding sleep hygiene and associated disorders which must be included as part of their curriculum (Goyal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%